Ameliorating effect of Berberis lycium root bark extracts against cisplatin-induced nephropathy in rat (Bangladesh Journal of Pharmacology, 2018)
The aim of this study was to investigate the sub-acute nephroprotective effect of Berberis lycium root bark extracts against cisplatin-induced nephrotoxicity. Aqueous and methanol extracts (200 and 400 mg/kg) were co-administered with cisplatin (4 mg/kg) for 19 days. Results showed that cisplatin significantly (ap